Analisis Literasi Informasi Mahasiswa Program Studi Ilmu Perpustakaan dan Informasi Islam Dalam Menilai Kepercayaan dan Kualitas Produk Pada Aplikasi Shopee - irsyad sholahuddin; Imam Mahmudi (Jurnal Gema Pustakawan, 2026)
The growth of e-commerce has driven an increase in online shopping activity through the Shopee app. This situation requires users to possess information literacy skills to accurately assess seller trustworthiness and product quality. This study aims to analyze the information literacy of students in the Islamic Library and Information Science Program in assessing seller trustworthiness and product quality on the Shopee app based on ACRL standards. The study employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation of the 2023 cohort of students who have experience shopping on Shopee. The results indicate that students possess fairly good information literacy skills in identifying information needs, accessing various sources, evaluating the credibility of information, and utilizing information as a basis for purchasing decisions. However, challenges remain, including difficulty distinguishing between genuine and fake reviews, as well as product information that is not entirely accurate.